Educação física, componente curricular ou prática esportiva : um olhar sobre as escolas estaduais do município de Várzea Grande MT - Figueiredo, Claudineia Paula (2018)
Physical Education in Brazil is marked by significant advances, which are precedents of struggles fought in the academic field, opening the way towards the conquest of its legitimation in the disciplinary field. This course has been braided with barriers that have been and still have been constantly overcome, with emphasis on pedagogical practice in School Physical Education that is a subject quite discussed in the area of knowledge. Thus, it becomes essential for the pedagogical practice of Physical Education in schools aiming to understand if/how this subject is realized from the curricular component presupposition. Thus, this study sought: Identify the way in which the subject Physical Education as a curricular and school discipline is treated in the school space, and, more specifically, Identify the concepts presented by managers and teachers about the importance of Physical Education at school; Identify how the a pedagogical coordination accompanies the subject Physical Education;To ascertain the possible difficulties faced by Physical Education teachers in the legitimization of the discipline as a curricular component. This research was developed in three Elementary Schools in Várzea Grande city, in Mato Grosso state. This study has the descriptive character of a qualitative character with a design in the case study. The instruments used to collect the data were; systematic analysis, documentary analysis and semi-structured interviews. The data were analyzed through the construction of categories and triangulations of documents and information acquired.The results of this study reveal a great fragility in the pedagogical practice of Physical Education teachers, which begins with the lack of clarity about the understanding of what Physical School Education is and extending to its behavior in relation to the discipline. However, there are good actions on the part of teachers as well, who distance themselves from a marginalized practice and without responsibility. With regard to the representations of pedagogical management, we have been able to identify through this research that there is a higher degree of responsibility for dealing with the discipline, starting with its equivalence to the other disciplines in the PPP of the schools. In the monitoring by the management with the discipline, it was possible to identify a new implementation by the State, which is present in the speech of the pedagogical coordinators of the three schools, but still little effective in the daily actions. Finally, we emphasize that the relation between teacher and management can establish positive relations in the legitimation of the discipline, when accompanied effectively by pedagogical coordination.